Random effect method to learn some basic skills of basketball - Ismail , mayad; Abdul Hassan, Muhannad (Journal of Physical Education, 2012)
The impact of random method to learn some basic basketball skillsI have cared involved in the field of education material basketball as a key material taught to students and factors affecting education is the teaching methods and learning styles, which has expanded and clear at the present time because of their importance in the education of students and raise their motivation and needs of cognitive and physical skills and that each style of teaching philosophy especially learning that it’s built on the basis of sincerity and persistence in the field of application and that these methods share one goal: to interest the student, the upgrading of all aspects and is therefore imperative for the teacher to select the best methods of learning to reach the goal as soon as time and less effort, and here lies the importance of Search Tathiralaslob random to learn some basic skills of basketball.goal of the research: the impact of indiscriminate use of technique to learn some basic skills of basketballHypothesis Search: the style of random positive effect statistically significant to learn some basic skills of basketball, has concluded the researcher hoc approach is the best way to learn the skills examined, from the traditional method used in the game of basketball, has recommended the adoption of ad-hoc approach to the preparation of curricula studied Education sports for the development of learning skills of students .